The emergence of core (hash)tags and its effects on performance. (August 2022) - Xu, Larry Zhiming; Sargent, Matthew; Xu, Yu; Sun, Jingyi; Li, Yiqi; Fulk, Janet
Highlights: Very few (hash)tags emerge as "core tags"-- the consensus choices. Using core tags noticeably improves users' performance than does peripheral tags. Core tags that are linguistically idiosyncratic particularly contribute to high performance. Abstract: The informational and social impacts of tags on forming networked publics have drawn extensive scholarly attention. However, existing literature lacks systematic and longitudinal accounts of how trending tags garner community interest and facilitate the promotion of user-generated content. This study addresses this issue by explicating the structures and functions of social tagging, showing how users employed certain tags to improve performance. To provide empirical evidence, we tracked and analyzed social tagging activities in an online community from its early stage for seven years. Over this time frame, very few tags emerged as core tags--the consensus choices that both occurred and co-occurred frequently. Furthermore, the application of core tags, which can represent the tacit rules and platform vernaculars co-defined by the community members, improved performance noticeably more than using peripheral tags. Interestingly, among the core tags, those that possessed linguistic idiosyncrasies particularly contributed to high performance. The findings highlight the complex contingencies of social tagging structures and functions and provide practical implications for users and platforms to strategically manage tag-based networked publics.